PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN BERFIKIR KREATIF SISWA DALAM PEMBELAJARAN IPAS SEKOLAH DASAR - Mayora Katharina Br. Sitinjak; Silalahi, Eka Kartika; Reflina Sinaga; Ester Julinda Simarmata; Heka Maya Sari Sembiring (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Creative thinking is an essential skill that needs to be developed in science and social studies learning at the elementary school level. This study aimed to determine the effect of the Discovery Learning model on students’ creative thinking skills in science and social studies learning among fifth-grade students at SD Negeri 060833 Medan Petisah. This research employed a quantitative approach using a pre-experimental method with a one-group pretest–posttest design. The subjects were 22 fifth-grade students. The research instrument was an essay test designed to measure creative thinking skills based on four indicators: fluency, flexibility, originality, and elaboration. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and a paired sample t-test at a significance level of 0.05. The results showed that students’ mean pretest score increased from 46.18 to 81.82 in the posttest, with an improvement of 35.636 points. The normality test showed that the data were normally distributed, with a significance value of 0.513 > 0.05. Furthermore, the paired sample t-test showed a significance value of 0.000 < 0.05, indicating that H₀ was rejected and H₁ was accepted. Therefore, the Discovery Learning model had a significant effect on students’ creative thinking skills. This model effectively encouraged students to generate ideas, provide varied answers, express original thoughts, and elaborate their responses in science and social studies learning.